Pengaruh implementasi guided discovery learning berbasis STEM terhadap hasil belajar matematika peserta didik - Rahman, Fatchiyah; Nugroho, Moch Rifaldi Mas; Fikrati, Ama Noor (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2025)
Basic trigonometry is one of the essensial materials for students to master. However, many students still have difficulty with this material. Therefore, an innovative learning model is needed, one of which is using STEM-based guided discovery learning. This study aims to investigate the effect of implementing a guided discovery learning model based on the STEM approach on basic trigonometry material phase E on the learning outcomes of class X students. This study uses a quantitative approach with a one-group pretest-posttest Design. Data were collected through diagnostic assessments as pretests and sub-summative assessments of the material as post-test. The sampling technique used saturated samples, with a population and sample of 27 class X2 students at Trimurti High School. Data analysis was carried out through a normality test using the Kolmogorov-Smirnov test and a comparative test using the Wilcoxon test. The normality test results showed a significance value of less than 0.05 (data was not normally distributed), so it was continued with the Wilcoxon test, which produced an Asymp.Sig value (2-tailed) 0.001. These results indicate a positive and significant effect of implementing a guided discovery learning model based on STEM on students' mathematics learning outcomes. This study is expected to provide an alternative for teachers in choosing collaborative learning models with approaches that can improve student learning outcomes and realize student-focused learning.